2017
DOI: 10.4097/kjae.2017.70.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Heated carrier fluids in decreasing propofol injection pain: a randomized, controlled trial

Abstract: BackgroundPropofol is a commonly used intravenous drug during anesthetic induction because of its rapid onset and short duration. However, the injection pain that patients experience is so severe that they recall the induction of anesthesia as the most painful part of the perioperative period. Therefore, the objective of this study was to determine the effect of heated carrier fluids (40℃) in decreasing propofol injection pain.MethodsA randomized, controlled clinical trial was conducted in 90 patients aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In addition, the suitability of the method for data collection must be tested. Let us review the study by Youn and Hsu [ 6 ], where the authors compared the methods for pain reduction with a propofol injection. In the pilot study, the following four methods were tested in order to find the most appropriate method for the main trial: Group T received an injection of 0.5 mg/kg of 1% lidocaine after applying a tourniquet; Group H received an injection of 0.5 mg/kg of 1% lidocaine after the injection of 40–41℃ saline solution (200 ml); Group L received an injection of 0.5 mg/kg of 1% lidocaine after an injection of room temperature (23–24℃) saline solution (200 ml); and Group HL received an injection of 0.5 mg/kg of 1% lidocaine at 41℃.…”
Section: Objectives Of a Pilot Studymentioning
confidence: 99%
“…In addition, the suitability of the method for data collection must be tested. Let us review the study by Youn and Hsu [ 6 ], where the authors compared the methods for pain reduction with a propofol injection. In the pilot study, the following four methods were tested in order to find the most appropriate method for the main trial: Group T received an injection of 0.5 mg/kg of 1% lidocaine after applying a tourniquet; Group H received an injection of 0.5 mg/kg of 1% lidocaine after the injection of 40–41℃ saline solution (200 ml); Group L received an injection of 0.5 mg/kg of 1% lidocaine after an injection of room temperature (23–24℃) saline solution (200 ml); and Group HL received an injection of 0.5 mg/kg of 1% lidocaine at 41℃.…”
Section: Objectives Of a Pilot Studymentioning
confidence: 99%
“…Other effective non-pharmacological approaches, or combinations of pharmacological approaches, have been recommended to relieve PIP including warming propofol, venous occlusion with a tourniquet, applying microfiltration and changing the lipid composition [3,12,17,23,24]. However, no method could eliminate PIP completely and most of these methods were not routinely available in clinical practice, except venous occlusion with a tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed various methods to alleviate PIP, including changing the injection speed, warming up propofol, choosing a large vein and the addition of some drugs [5][6][7][8][9][10][11][12][13]. At present, lidocaine is the most common drug used to relieve PIP.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated rate (90 mg/h) was insufficient to control acute pain and was lower than that used in this study (108 mg/h). We referred to previous studies of the relationship between temperature and pain during injection [ 12 13 14 ], in hopes of finding a way to infuse quickly with minimal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that injection pain is reduced by thermal vasodilation [ 12 13 14 ]. While several studies reported vasodilatory effects after heating for more than 20 minutes [ 21 22 23 ], it is doubtful whether heating for less than 5 minutes caused vasodilatory effects in previous studies, or in this study.…”
Section: Discussionmentioning
confidence: 99%